From marine caves to the deep sea, a new look at Caminella (Demospongiae, Geodiidae) in the Atlanto-Mediterranean region - Cárdenas, Paco; Vacelet, Jean; Chevaldonné, Pierre; Pérez, Thierry; Xavier, Joana R. (Zootaxa, 2018)
Caminella Lendenfeld, 1894 is a poorly known Geodiidae genus with unclear phylogenetic relationships. In order to find new lines of evidence that could shed light on the evolutionary history of Caminella, we decided to revise type material and museum material, as well as examine new material from underwater caves and deep-sea ecosystems. In doing so, we formally show that Isops maculosus Vosmaer, 1894 and Caminella loricata Lendenfeld, 1894 are junior synonyms of Caminella intuta (Topsent, 1892). We discuss different spicule morphological phenotypes in C. intuta, which may be linked to silica availability. We also discovered two new species of deep-sea Caminella: 1) from Cape Verde (Caminella caboverdensis sp. nov.) and 2) from seamounts located south of the Azores archipelago and the North of Spain (Caminella pustula sp. nov.). We reveal that Caminella sterrasters have complex surface microstructures, unique amongst the Geodiidae, where actin tips are linked to each other. Molecular markers (COI, 28S (C1-D2) and 18S) sequenced for some specimens led to new phylogenetic analyses, which continue to suggest a close relationship of Caminella with the Erylinae and Calthropella; these affinities are discussed in light of morphological characters.